Cautious about Conatives - Malone, Andrew S. (Novum Testamentum, 2020)
It has long been recognized that the imperfect and present tenses can communicate a conative sense. The category is sufficiently established that New Testament commentaries can brusquely identify “a conative imperfect” or “imperfectum de conatu” as if (1) the terminology conveys a uniform meaning and (2) such meaning is established by the verb’s tense. A fresh inspection of the phenomenon suggests neither assumption is accurate. With worked examples we can observe that at least two competing nuances are understood by the label “conative” and that the verb’s tense is far from the determinative factor. Whether in generating claims about the conative sense or in digesting others’ analyses, interpreters need to be alert to the pitfalls associated with this category.